Attitudes of university students towards the uses of electronic newspapers - Randa Karim Marzouk; Karrar Rashid Qasim (Genius Journals, 2024)
The current descriptive study aims to identify the attitudes of university students towards the uses of electronic newspapers among university students in Thi Qar Governorate. The study sample consisted of 300 students from various universities, and the sample for the design and construction of the scale was 150 students, and the sample for the application was 150 students, who were randomly selected by the researchers in the second semester of the academic year 2023/2024. The discriminatory power of the items was used to detect strong items and weak items, as well as the internal consistency of the items to determine the relationship of the item to the total score of the scale. The researcher used split-half and Cronbach's alpha to detect the stability of the scale. The results showed that the electronic press is a source of information gathering and is more popular than the paper press. It is accessible to all university students, has the largest amount of information and is the fastest in its spread. Electronic newspapers are more independent and give a degree of credibility to the reader. Based on the results of the current study, a set of recommendations were proposed by the researchers at the end of the study
Keywords: Electronic newspapers; direction